Hölder Regularity for the Linearized Porous Medium Equation in Bounded Domains (Analysis in Theory and Applications, 2024)
In this paper, we systematically study weak solutions of a linear singular ordegenerate parabolic equation in a mixed divergence form and nondivergence form,which arises from the linearized fast diffusion equation and the linearized porousmedium equation with the homogeneous Dirichlet boundary condition. We prove theHölder regularity of their weak solutions.
Keywords: Singular parabolic equations; degenerate parabolic equations; regularity; porous medium equations.